Microfluidic very large scale integration (VLSI) : modeling, simulation, testing, compilation and physical synthesis /: modeling, simulation, testing, compilation and physical synthesis. (2016) - Pop, Paul; Minhass, Wajid Hassan; Madsen, Jan
No abstract available